Pengaruh Human Capital dan Komitmen Organisasi Terhadap Kinerja Karyawan pada Labersa Toba Hotel & Convention Center di Kota Balige - Mijy Swandi Tanjung; Edison Sagala (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of Human Capital and Organizational Commitment on employee performance at Labersa Toba Hotel & Convention Center in Balige City. The population in this study were all employees of Labersa Toba Hotel & Convention Center with a sample size of 129 employees, selected using total sampling techniques. This study uses a quantitative approach with a data collection instrument in the form of a questionnaire. Data analysis techniques used include validity tests, reliability tests, classical assumption tests, path analysis, and upsilon (v) tests. The results of the study indicate that there is a significant influence between Human Capital on employee performance. There is a significant influence between Organizational Commitment on employee performance, There is a significant influence between Human Capital on Organizational Commitment. Indirectly, there is an influence of Organizational Commitment in Mediating the influence of Human Capital on Employee Performance at Labersa Toba Hotel & Convention Center in Balige City. This study provides recommendations to companies to pay attention to aspects of Human Capital and organizational commitment in order to achieve company targets.